In vivo optical imaging correlates with improvement of cerebral ischemia treated by intravenous bone marrow stromal cells (BMSCs) and edaravone. (1st December 2013) - Tian, FengFeng; Yamashita, Toru; Deguchi, Kentaro; Omote, Yoshio; Kawai, Hiromi; Ohta, Yasuyuki; Abe, Koji
<x xml:space="preserve">Abstract</x> Objective: Recent studies show that modern In vivo optical imaging can detect matrix metallopeptidase (MMP) activation in the ischemic brain. In this study, we analyze the protective effects of bone marrow stromal cells (BMSCs) and edaravone (EDA) against tissue plasminogen activator (tPA) risk in the ischemic brain with In vivo optical fluorescence MMP imaging. Methods: At 48 hours after 60 minutes of transient middle cerebral artery occlusion (tMCAO) with tPA, C57BL/6J mice were subjected to motor function analysis, In vivo and ex vivo optical imaging for MMP activation, gelatin zymography, and double immunofluorescent analyses with or without intravenous BMSC transplantation and the intravenous free radical scavenger EDA. Results: In vivo fluorescent signals for MMP were detected over the heads of living mice 48 hours after tMCAO; the strongest were in the tPA group, which were reduced by BMSC or EDA treatment. These In vivo data were confirmed by ex vivo fluorescence imaging. While massive intracerebral hemorrhages were observed in the ischemic hemispheres of the tPA group, only slight hemorrhages were found in the tPA/BMSC, tPA/EDA, and EDA groups. Gelatin zymography showed the strongest MMP-9 activation in the tPA group after tMCAO, which was reduced by BMSC or EDA treatment. Conclusion: The present study provides a correlation between In vivo optical imaging of MMP activation and the improvement of ischemic brain damage caused by tPA after tMCAO and treated by BMSC and EDA.